Risk of new-onset polymyalgia rheumatica following COVID-19 vaccination in South Korea: a self-controlled case-series study - Ju-Young Shin; Hyoun-Ah Kim; Ju Hwan Kim; Jieun Woo; Mu Kyung Kim; HyunJoo Lim; Hyunah Jung (RMD Open)
Background While several studies have reported some cases of polymyalgia rheumatica (PMR) following COVID-19 vaccination, studies using large databases are lacking.Objectives To investigate the risk of PMR after COVID-19 vaccination using self-controlled case series (SCCS) analysisMethods We used the National Health Insurance Database, linked with the COVID-19 registry between February 2021 and August 2023, to identify adults aged 50 years or older who received at least one dose of COVID-19 vaccine and subsequently diagnosed with PMR within the observation period, defined as 240 days after the first dose of vaccine. The risk window was defined as 28 days after each dose of COVID-19 vaccination, and the control window encompassed the remainder of the observation period. Incidence rate ratios (IRRs) were estimated using conditional Poisson regression with 95% CIs, stratified by dose and vaccine type.Results Among 44 818 078 COVID-19 vaccine recipients, 376 patients were diagnosed with PMR. The analysis indicated that COVID-19 vaccination was not associated with an increased risk of PMR (IRR, 0.74; 95% CI 0.59 to 0.94). Rather, the risk of PMR was slightly reduced after the first dose (0.52; 0.34 to 0.79), with no significant association with other doses of COVID-19 vaccine (0.83; 0.59 to 1.16 for second dose, 0.77, 0.48 to 1.25 for third dose).Conclusion In this nationwide SCCS, there was no association with the increased risk of PMR following COVID-19 vaccination. While these findings support the safety of COVID-19 vaccines, interpretation of the decreased risk of PMR should be cautious.